Malignant Mesenchymal Tumors of the Breast: Current Challenges and New Perspectives on Primary Sarcomas and Malignant Phyllodes Tumors - Flavia De Lauretis; Alejandro Martin Sanchez; Cristina Accetta; Beatrice Carnassale; Sabatino D’Archi; Alba Di Leone; Antonio Franco; Federica Gagliardi; Stefano Magno; Elena Jane Mason; Francesca Moschella; Lorenzo Scardina; et al. (Life)
Mesenchymal tumors of the breast constitute a rare and heterogeneous group of neoplasms, representing only 0.5% to 1% of all breast tumors. Originating from mesenchymal tissues, these tumors include various histological subtypes. They are particularly aggressive, characterized by a high propensity for local recurrence and an overall poor prognosis. The rarity of these cases has impeded the development of comprehensive clinical studies, leading to a lack of standardized diagnostic protocols and treatment guidelines. This review provides a thorough synthesis of current knowledge on breast mesenchymal tumors with a specific focus on malignant variants such as phyllodes tumors and breast sarcomas. It also addresses the diagnostic challenges faced by clinicians, evaluates current therapeutic strategies, and emphasizes the crucial role of surgical treatment. Additionally, it examines the evolving roles of chemotherapy and radiotherapy in enhancing patient outcomes.